Financing and Delivering Pre-Exposure Prophylaxis (PrEP) to End the HIV Epidemic. (2022) - Killelea, Amy; Johnson, Jeremiah; Dangerfield, Derek T.; Beyrer, Chris; McGough, Matthew; McIntyre, John; Gee, Rebekah E.; Ballreich, Jeromie; Conti, Rena; Horn, Tim; Pickett, Jim; Sharfstein, Joshua M.
Abstract: The U.S. has the tools to end the HIV epidemic, but progress has stagnated. A major gap in U.S. efforts to address HIV is the under-utilization of medications that can virtually eliminate acquisition of the virus, known as pre-exposure prophylaxis (PrEP). This document proposes a financing and delivery system to unlock broad access to PrEP for those most vulnerable to HIV acquisition and bring an end to the HIV epidemic.